QTL Mapping of Seed Glucosinolate Content Responsible for Environment in Brassica napus - He, Yajun; Fu, Ying; Hu, Dingxue; Wei, Dayong; Qian, Wei (Frontiers in Plant Science, 2018)
Glucosinolates (GSLs) are a major class of secondary metabolites. The content of seed GSL is largely regulated by environments in rapeseed (Brassica napus). However, the genetic control of seed GSL content responsible for environment in Brassica napus has been poorly understood. In the current study, a doubled haploid (DH) population from a cross between winter and semi-winter lines of rapeseed was grown in two distinct eco-environments, Germany and China, to evaluate the eco-environment effect and dissect the quantitative trait loci (QTLs) responsible for environment for seed GSL in rapeseed. The deviation value of GSL content between eco-environments (GSLE) was calculated for each line in the DH population and the QTLs for GSLE were detected. GSLE ranged from -46.90 to 36.13 μmol g–1 meal in the DH population, suggesting the prominent eco-environmental effects for seed GSL in rapeseed. Four QTLs for GSLE were identified on chromosomes A04, A06 and A09, explaining 4.70～9.93% of the phenotypic variation. Comparison of QTLs of seed GSL content between different eco-environments found three QTLs for GSL on A02 from 37.6 cM to 45.4 cM, A04 from 0 cM to 17.2 cM and A09 from 67.0 cM to 98.6 cM, exhibited significant difference of QTL effect between the German and Chinese eco-environments (P < 0.01), indicating the environment sensibility of these loci on seed GSL content. Moreover, flowering time (FT), an important environment adaptation trait in plant, was also investigated in this study. Comparative QTL analysis among GSLE, GSL and FT revealed that three regions on chromosomes A02, A04 and A09, not only exhibited significant differences in QTL effect between Germany and China, but also co-located with the QTL intervals of GSLE and FT. Our results revealed that most of the GSL loci can influence GSL accumulation under different eco-environments, whereas the three QTL intervals on A02, A04 and A09 might be sensitive to the eco-environments for seed GSL content.